Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, December 11, 1929 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1929)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, December 11, 1929. Simon Cameron was Lincoln’s secretary of war. He was a politician, the first of a line who have made Pennsylvania politics notorious. Cameron’s definition of an honest man in politics was “One who may be bought and will stay bought.” The odor of scandal had attached to his administration of certain Indian affairs. In 1860, he was a rival of Lincoln in the republican convention and his appointment to a cabinet place was supposedly the price Lincoln’s managers paid to get Cameron out of the field. Hawley disliked and distrusted Cameron.
1 electronic record. Scanned newspaper article. 2 image scans. 1.33 MB (1,404,497 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 38.1 MB (39,996,501 bytes).
Keywords: United States--History--Civil War, 1861-1865; Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); Personal correspondence; Letters; Newspapers